Impact of the O/P ratio on the optical properties and structures of fluoride–phosphate glass. Issue 5 (17th January 2023) - Yoshimoto, Kohei; Ueda, Motoi; Yamamoto, Yuya; Mizuguchi, Masafumi
Abstract: Ca(PO3 )2 –AlF3 –CaF2 –BaF2 –BaO glasses were prepared by the melt quenching method, and the effects of the O/P ratio on the optical properties and glass structure were investigated. The bandgap energy showed no significant change at O/P = 3.0–3.4 but drastically decreased with the increase in the O/P from 3.6 to 4.0. In addition, the refractive index dispersion was analyzed based on the Lorentz model, and it was found that the decrease in the resonance frequency in the ultraviolet region with the increase in the O/P ratio resulted in an increase in the refractive index and dispersion. Analysis of the infrared absorption and Raman scattering spectra revealed that the phosphate chains were broken, and isolated Q 0 units were generated with the increase in the O/P ratio from 3.6 to 4.0. Based on the structural change of the glass, the origin of the nonlinear dependence of the optical properties on the O/P ratio was discussed.